Features of immune reactions in leaves and tubers of Solanum tuberosum plants during infection by Pectobacterium versatile bacteria - Kalubaka, Nastassia V.; Hryhoryeva, Nadzeya A.; Shrub, Katerina V.; Nikolaichik, Yevgeny A. (Experimental Biology and Biotechnology, 2026)
We analysed the expression patterns of genes of the main components of hormonal regulation in leaves and tubers of potato plants infected with Pectobacterium versatile bacteria to identify hormonal status-dependent immune defense mechanisms. Based on gene expression data for abscisic acid biosynthesis, it is suggested that the amount of the active form of this acid decreases. Suppression of jasmonate-dependent gene expression was observed. Ethylene-dependent transcription factors were shown to be expressed in different directions in potato leaves and tubers.
Keywords: molecular phytopathology; Solanum tuberosum; Pectobacterium versatile; hormonal regulation of plant immunity